Agricultural Mechanisation in Nigeria: the Prospects and Promises - Makanjuola, G. A. (Obafemi Awolowo University Press, 2013)
The application of technological innovations to the solution of problems is perhaps the single most important factor responsible for human progress. This inaugural lecture addressed: importance and role of agricultural mechanisation as a vehicle for agricultural production; problems faced by Agricultural Engineering as a profession; present state of mechanisation in Nigerian agriculture; type and level of mechanisation appropriate to our farming system; contribution of the University of Ife to agricultural mechanization in Nigeria; and challenges of ensuring that our future mechanisation programmes are meaningful and fruitful.